ANALISIS PENGARUH PDRB, JUMLAH INDUSTRI DAN JUMLAH PENDUDUK TERHADAP RETRIBUSI KEBERSIHAN SAMPAH TAHUN 1990 – 2021 - Tamin, Alysha Kadeezah Akmal; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
In order to achieve their objectives of development and governmental activities, local governments need to increase their Local Own-Source Revenues, which consist of local levy. The purpose of this study is to find empirical evidences regarding factors influencing the amount of income from garbage levy in Malang city. This research examines the city’s GRDP, number of industries, population, and levy on garbage management from 1990 to 2021. Using classical assumption test and significance test, the data analysis results indicate that GRDP and population have positive and significant effects on cleanliness levy and that number of industries has an insignificant negative influence on the levy